Compressive Deformation Behavior of Artificial Pumice for Reinforcement of Existing Shelter Against Ballistic Ejecta of Volcanic Eruption - Kohei Tateyama; Kazuma Abe; Hiroyuki Fujiki; Hisashi Sasaki; Hiroyuki Yamada (Applied Mechanics)
The 2014 Mt. Ontake eruption in Japan highlighted the need for improved volcanic shelters. To contribute to their reinforcement, this study focuses on the energy absorption characteristics of pumice, particularly artificial pumice made from waste glass. Compression tests were conducted under unconfined and oedometric conditions using a universal testing machine, drop-weight testing machine, and split Hopkinson bar across a wide strain rate range (10−3 to 102 s−1). The deformation behavior was categorized into two types: one with a distinct initial peak followed by stress drop and another with a continuous transition to plateau deformation. Regardless of deformation type, the absorbed energy showed a positive dependence on strain rate. The average absorbed energy increased from approximately 1.6 MJ/m3 at 10−3 s−1 to over 4.3 MJ/m3 at 102 s−1. A simple predictive model was proposed to evaluate the energy absorption capacity of pumice reinforcement. The model’s predictions were in good agreement with experimental results for pumice layers up to 150 mm thick. These findings provide fundamental insights into the high strain rate behavior of artificial pumice and its potential application as a passive energy-absorbing material for impact-resistant volcanic shelters.